Teacher and learner beliefs and expectations about English language teaching and learning at a Mozambican university - Nhapulo, Marcos Abilio (Afrika Focus, 2013)
Recent studies have suggested that teacher and learner beliefs about second language instruction have a significant influence on language teaching and learning process and, consequently, on students’ achievements. However, in the Mozambican context, we still do not have studies focusing on learner and teacher beliefs about students and language proficiency, about teaching materials, about individual and cultural variations and beliefs about the learning process itself. Using ques- tionnaires and a focus group report, we look at the Mozambican linguistic profile, the learner and teacher beliefs and their influence in tertiary English Language Teaching (ELT) and learning. The results show that there is a need for creating an environment in which teachers’ and learners’ cultural background, beliefs and needs are considered so as to enable teachers to teach effectively, as well as enabling learners to achieve positive learning outcomes. Key words: beliefs, expectations, English Language Teaching, Mozambican students, Mozambique, second language learning